Qualitative Methods and Hybrid Maps for Spatial Perception with an Example of Security Perception - Mandy Töppel; Christian Reichel (Urban Planning, 2021)
The security/insecurity of our cities has become the subject of public debate in recent years. The individual intuitions about security or insecurity can vary with age, gender, social background, personal constitution and previous positive or negative experiences. They are also constantly (re)produced, as perceptions of space are individual and selective. Noting these variations, materialised factors also play a major role, e.g., recessed house entrances, dense or high hedges, poor orientation options, dark places, etc. Attributing meaning to these materialised factors, real constructs are formed which create positive or negative narratives about certain (urban) spaces, influencing the actual use and design of urban spaces. To investigate the importance attached to certain spaces, qualitative methods are required for examining socio-spatial situations, perceptual processes and attribution. Using different methods in an explorative and in-depth descriptive research phase, such as expert interviews, user observations, surveys on go-alongs, participatory mapping with detailed information on structural and spatial locations, the advantages and disadvantages of method selection are presented. Berlin's Alexanderplatz was used as a case study area to determine perceptions of security in urban areas. We confirmed that despite variations, certain subjective perceptions concerning visibility, brightness, and audibility are collective. Additionally, hybrid maps are used to explain how subjective perceptions of space, combined with 3D graphics, can alert architects and city planners to uncertainty among users of public space.
Keywords: 710; 3D planning tools; go alongs; hybrid maps; participatory mapping; spatial perception; urban resilience